1974
DOI: 10.1007/bf00153949
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and study habits

Abstract: The first part of the article reviews the literature (mainly British) on the relationships between academic performance in higher education and motivation and study habits. The distinction between goal-orientated and intrinsic motivation is used to clarify the meaning of previous studies. Among the investigations of study habits, the dimension of syllabus-boundness/syllabus-freedom helps to relate psychiatric work on study difficulties to research using self-report inventories.The weakness of the questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 19 publications
1
28
0
1
Order By: Relevance
“…Study methods were also found to be related to personality, indicating that students with differing personality and motivation were likely to study in contrasting ways (Entwistle et al, 1974). Even in this early research, the complexity of interrelationships affecting different ways of studying was becoming clear.…”
Section: Developing Inventory Measures Of Study Strategies Learning mentioning
confidence: 93%
“…Study methods were also found to be related to personality, indicating that students with differing personality and motivation were likely to study in contrasting ways (Entwistle et al, 1974). Even in this early research, the complexity of interrelationships affecting different ways of studying was becoming clear.…”
Section: Developing Inventory Measures Of Study Strategies Learning mentioning
confidence: 93%
“…These sources include the Lancaster group (Entwistle and Wilson, 1970;Entwistle, Thompson and Wilson, 1974), the Australian group (Biggs, 1978;1987a), the Swedish group Saljo, 1976a, 1976b), and the Richmond group (Pask, 1976). Some researchers have adopted quantitative methods based on psychometric techniques (Biggs 1987a, Entwistle andWilson, 1970), whereas others used more qualitative methods, for example, the phenomenographical approach (Lucas, 2001).…”
Section: Approaches To Learning Of Accounting Studentsmentioning
confidence: 99%
“…9 Returning to higher education, students with high scores on either fear of failure or hope for success were interviewed to explore their reactions to the situations they were meeting in higher education. 10 The most striking difference was in their comments about examinations. Students motivated by hope for success found that nervousness helped.…”
Section: Measuring Motivation To Learnmentioning
confidence: 94%